Rumen microbial responses to antinutritive factors in fodder trees and shrub legumes - McSweeney, C.S.; Odenyo, A.A.; Krause, D.O. (Informa UK Limited, 2002)
The major limitation to ruminant production in many tropical regions of Africa, Asia and Australia is poor nutrition. Annual growth rates of animals are restricted by the low nitrogen and high fiber content of the native grasses and crop residues that form the basis of the diets in these regions. Supplementation of tropical roughages with fodder trees and shrubs (FTS) is a promising method to alleviate nutrient deficiencies associated with these basal diets. However, FTS often contain toxins and anti-nutritional factors (ANFs) that limit their use as feedstuffs. Selection and breeding for cultivars that are low in toxins/ANFs has not been successful since the presence of these compounds is strongly associated with survival in many tropical environments. A solution to the problem may be the rumen microorganisms from adapted domestic and wild ruminants that have evolved rumen fermentation mechanisms to transform or detoxify some of these plant secondary compounds. This review examines the use in ruminant feeding systems of FTS that contain deleterious secondary compounds; our current understanding of microbial interactions with these secondary compounds, and advances in the use of rumen biotechnology to overcome these limitations.